2023
DOI: 10.1371/journal.pone.0285808
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic characteristics and equivalent crack width of coal and rock bodies around boreholes during progressive failure

Abstract: The ultrasonic characteristics of the coal and rock bodies around boreholes during failure are closely related to the crack propagation law. To investigate the ultrasonic characteristics and crack propagation law of coal and rock bodies around boreholes, different grouting samples with boreholes were taken to carry out ultrasonic test during progressive failure. The ultrasonic amplitude, velocity and attenuation coefficient of the samples were analyzed. According to the ultrasonic time difference formula, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…There are pores and cracks in the interiors of materials such as backfill body and rock masses. The characteristics and spatial distribution of the pores and cracks will affect strength, permeability, and durability [ 7 , 8 ]. Zhou [ 9 ] found that the geometric parameters of the original cracks and die angles of rock samples have a significant impact on their peak force by using a digital image correlation analysis (DIC) system and compression shear tests.…”
Section: Introductionmentioning
confidence: 99%
“…There are pores and cracks in the interiors of materials such as backfill body and rock masses. The characteristics and spatial distribution of the pores and cracks will affect strength, permeability, and durability [ 7 , 8 ]. Zhou [ 9 ] found that the geometric parameters of the original cracks and die angles of rock samples have a significant impact on their peak force by using a digital image correlation analysis (DIC) system and compression shear tests.…”
Section: Introductionmentioning
confidence: 99%